1992
DOI: 10.2307/1966530
|View full text |Cite
|
Sign up to set email alerts
|

Abortions in a Hospital Setting: Hidden Realities in Dar es Salaam, Tanzania

Abstract: This study investigates the extent of unwanted pregnancy, the use of illegally induced abortion, and the attitudes toward and practice of contraception among women admitted to a hospital with the diagnosis of abortion in Dar es Salaam, Tanzania. (In Tanzania, induced abortion is permitted only to save the mother's life.) A random sample of 300 women with early pregnancy loss admitted to Muhimbili Medical Centre, the teaching hospital in Dar es Salaam, were interviewed between September and November 1987, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 3 publications
3
25
0
1
Order By: Relevance
“…Even more disconcerting was that after a pregnancy loss, women were not given family planning information or supplies to space their next pregnancy [9]. Restrictive national laws, lack of access to safe abortion and lack of quality post-abortion car have led to the premature death of millions of mothers [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Even more disconcerting was that after a pregnancy loss, women were not given family planning information or supplies to space their next pregnancy [9]. Restrictive national laws, lack of access to safe abortion and lack of quality post-abortion car have led to the premature death of millions of mothers [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In settings where access to abortion is highly restricted and desire to regulate fertility is low, deaths due to abortion is a major contributor to maternal mortality [3]. In Tanzania, the law on abortion is highly restrictive and does not permit termination of pregnancy except when it is needed to save the life of a woman [4]. Consequently, women frequently resort to clandestine abortion performed by unskilled practitioners, leading to high rates of maternal mortality and morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of the problem of unsafe abortion at the community level in Tanzania is unknown, but hospitalbased studies on the incidence of complicated, incomplete abortions indicate that such terminations are common. 6 It has been estimated that unsafe abortion is a contributory factor in 15% of maternal deaths in Dar es Salaam. 5 Studies in sub-Saharan Africa have shown that women who have undergone illegal abortion are reluctant or unwilling to discuss their experiences for fear of negative personal, social, legal, and even medical consequences.…”
mentioning
confidence: 99%